Novel Biopolymer-Based Composite Wound Healing Wafers Containing Astragalus sarcocolla Gum - Nessa Bayat; Joshua S Boateng (University of Huddersfield Press, 2022)
The aim of this research was the formulation development, optimisation and characterisation of wafers produced from various combinations of carrageenan and tragacanth gum as potential carriers for wound healing extracts. Gels composed of one of the following three polymers: carrageenan (CAR), tragacanth gum (TG) and hydroxypropyl methylcellulose (HPMC) were prepared and freeze dried to obtain single polymer blank wafers. The blank wafers were examined for required lyophilisation behaviour and physical elegance of the resulting product. Based on these results, HPMC was eliminated and a combination of CAR:TG at seven different polymer ratios was chosen for further research. These CAR:TG wafers were characterised using scanning electron microscope (SEM), X-ray diffraction(XRD), texture analysis (hardness and mucoadhesion), Fourier transform infraredspectroscopy (FTIR), swelling tests and fluid handling properties. The formulations with the optimal properties were selected for loading with the extract and the drug-loaded wafers were subsequently further characterised as above.